A comparison of the effects of fire needle and routine acupuncture for myofascitis: A protocol for systematic review and meta-analysis. Issue 23 (11th June 2021) - Xiong, Wei; Cheng, Ling; Zhong, Zhiying; Hou, Xinju; Zhu, Manhua; Zhou, Xingchen; Zhu, Siyuan; Chen, Jun
Abstract: Background: Myofascitis is a common disease in clinic. The main cause of the disease is aseptic inflammation of local muscles and connective tissues such as myofascial, which can be manifested as paralysis, distension, and other discomfort, local muscle stiffness, spasm or palpable strain-like nodules. Chinese medicine ascribes it to "bi disease" and "Arthralgia disease, " while Western medicine believes that the disease is mainly due to local muscle and fascia edema and exudation caused by trauma or long-term strain, forcing nerves to jam and producing pain and other abnormal feelings. Although the disease is not life-threatening, the pain and distension caused by local inflammatory stimuli can affect the patient's daily life and sleep quality. The purpose of this systematic review is to evaluate the efficacy of fire needle vs routine acupuncture in the treatment of myofascitis. Methods: Randomized controlled trials (RCTS) of fire needle vs routine acupuncture for myofascial inflammation will be comprehensively searched from inception to September 2020 on PubMed, Embase, Cochrane Library, China Biomedical Literature (CBM), China National Knowledge Infrastructure (CNKI), Chongqing VIP (CQVIP), and Wanfang. Additionally, RCT registered sites, including http://www.ClinicalTrials.gov and http://www.chictr.org.cn, also will be the search. Visual analogue scale (VAS) was used to score the pain before and after treatment. The primary outcome will be to compare the difference in pain scores between the 2 interventions. Two independent authors filtered the literature in the above database, extracted the data, and cross-checked it. Results: This study will offer a reasonable comprehensive evidence for the treatment of myofascitis with fire needle. Conclusion: The conclusion of this study will provide evidence to judge the effectiveness of fire needle on myofascitis. Registration number: INPLASY202080034.